Pertanggungjawaban Pemerintah dalam Kebijakan Penataan Pegawai Non Aparatur Sipil Negara Dikaitkan dengan Sistem Merit - Mutia, Aisha RH (Nagari Law Review, 2025)
The structuring of non-civil servant employees (non ASN) constitutes a constitutional mandate that must be fulfilled by the government within the timeframe stipulated in Law Number 20 of 2023 on the State Civil Apparatus. This study analyzes government accountability in the structuring of non-ASN employees in relation to the implementation of the merit system as the foundation of bureaucratic reform. Employing a normative juridical method with a qualitative approach, the research evaluates legal, implementative, and systemic aspects of non-ASN employee structuring. The findings reveal that government accountability in managing non-ASN employees faces complex challenges in the implementation of the merit system, which significantly affects the overall effectiveness of bureaucratic reform. The study concludes that government accountability in the structuring of non-ASN employees is not only legal-administrative in nature but also constitutional, considering the state’s obligation to provide legal certainty and protection for citizens who have served. These findings contribute to the development of the theory of state administrative accountability and provide recommendations for improving personnel policies to be more equitable and merit-based.